Reading development and the teaching of reading : a psychological perspective - Oakhill, Jane.; Beard, Roger (Oxford, UK : Malden, Mass. : Blackwell Publishers, 1999)
This text aims to demonstrate how psychological research contributes to the understanding of both the nature of literacy and reading development with particular emphasis for practitioners.
Includes bibliographical references and indexes.
Keywords: Reading; Reading, Psychology of